2018
DOI: 10.1590/1678-4162-97330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 0.15% sodium hialuronate and 0.5% carboxymethylcellulose on tear film breakup time in healthy dogs and in dogs with keratoconjunctivitis sicca

Abstract: This study aimed to evaluate the effect of the 0.15% sodium hyaluronate (SH) and of 0.5% carboxymethylcellulose (CMC) on tear film breakup time (TFBUT) in 10 healthy dogs and in 32 eyes of dogs with keratoconjunctivis sicca (KCS). In addition, the goblet cell density (GCD) of this population was quantified. TFBUT was assessed at baseline and at different time points following the instillation of SH and CMC. KCS was graded as mild, moderate, and severe. GCD were quantified from conjunctival biopsies. The number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…One study showed that the hourly application of one drop of carmellose sodium or 0.25% hyaluronic acid provided 100% protection against corneal ulceration and 90% protection against corneal abrasions in non‐brachycephalic dogs undergoing general anesthesia for non‐ophthalmic procedures 22 . In the current study, the authors decided to use 0.15% SH, since it has been reported that this lubricant lasted longer periods on the ocular surface of dogs with keratoconjunctivitis sicca than 0.5% carboxymethylcellulose 23 . In addition, the time point of instillations adopted in our study was decided based on pilot studies.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…One study showed that the hourly application of one drop of carmellose sodium or 0.25% hyaluronic acid provided 100% protection against corneal ulceration and 90% protection against corneal abrasions in non‐brachycephalic dogs undergoing general anesthesia for non‐ophthalmic procedures 22 . In the current study, the authors decided to use 0.15% SH, since it has been reported that this lubricant lasted longer periods on the ocular surface of dogs with keratoconjunctivitis sicca than 0.5% carboxymethylcellulose 23 . In addition, the time point of instillations adopted in our study was decided based on pilot studies.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, the isolated effect of each drug used in the current anesthetic protocol on TFBT should be determined in further studies. Previous studies have described TFBT as being effective in evaluating the retention time of ophthalmic lubricants on the ocular surface of humans, dogs, and laboratory animals 12–19,23 . However, the authors suggest that further studies should be carried out using fluorophotometry, a method considered to be the gold standard in assessing tear dynamics, 25,26 instead of TFBT.…”
Section: Discussionmentioning
confidence: 99%
“…However, this parameter tended to return to 12.15 s, which is above the 10 s reported to be considered normal in evaluations carried out using traditional TFBT. 20,32 Regarding the potential clinically harmful effects of topical NSAIDs on the ocular surface of dogs, one study reported that the instillation of topical flurbiprofen did not cause conjunctival hyperemia, aqueous flare, or blepharospasm. 9 Likewise, signs related to ocular discomand inflammation were not seen in the eyes that received FTK and BACKT.…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria for selection of dogs included brachycephalic breed, current or recent (30 days before) treatment with any systemic or topical ophthalmic medications, Schirmer tear test-1 with values ≤15 mm/min., a tear film breakup time of less than 10 s, 20,32 current/history of abnormalities in the adnexa (previous surgery), current/history of ocular surface disease, or current/history of intraocular diseases such as uveitis or cataracts detected on full ophthalmic examination. Additionally, only dogs without systemic comorbidities, as assessed by general physical examination and laboratory work (blood cell count, albumin, alanine aminotransferase, alkaline phosphatase, urea, creatinine, lactate, sodium, potassium, and urinalysis).…”
Section: Dogsmentioning
confidence: 99%
See 1 more Smart Citation